On the spectral response measurement of multijunction solar cells - Garcia, Javier Andrés; Socolovsky, Hernán Pablo; Plá, Juan Carlos (IOP Publishing, 2017)
Fil: García, Javier Andrés. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina